1775 Mass. Acts 15 - (:unkn) unknown (My University, 1775)
An Act For Forming And Regulating The Militia Within The Colony Of The Massachusetts Bay, In New England, And For Repealing All The Laws Heretofore Made For That Purpose, ch. 1, §§ 1,7,9: § 1. . . That that part of the militia of this Colony, commonly called the Training-Band, shall be constituted of all the able-bodied male persons therein, from sixteen years old to fifty [excepting Quakers and others]. . . § 7. . . That each and every officer, and private soldier of said militia, not under the controul of parents, master, or gaurdians, and being of sufficient ability therefor, in the judgement of the select-men if the town wherein he has his usual place of abode, shall equip himself, and be constantly provided with a good firearm. . . § 9 . . . That the clerk of each and every company of said militia, shall . . . take an exact list of his company, and of each man's equipment respectively. .
Keywords: ARMED FORCES